IKLIM ORGANISASI SEKOLAH DAN PENGARUHNYA TERHADAP TINGKAT MOTIVASI KERJA GURU SMA NEGERI DI KABUPATEN SIDOARJO - Vina Lailatun Nisfa; Burhanuddin Burhanuddin; Wildan Zulkarnain; Vina Lailatun Nisfa; Burhanuddin Burhanuddin (Universitas Negeri Malang, 2024)
Abstract: This research was conducted to know the climate condition of the state high school organization in Sidoarjo, the motivation level of high school teachers in Sidoarjo district, and the influence between the organization's climate with the motivation level of the work of high school teachers in Sidoarjo district. A quantitative approach with simple linear regression analysis is used in this study. The results showed that the organizational climate condition and the motivation level of the work of high school teachers in Sidoarjo Regency are in the low category, as well as in both variables that are the climate of the organization with the motivation of working high school teachers in Sidoarjo is a positive influence